Bagaimana Keberlakuan Hak Waris di Indonesia - Immanuel Rich, Johannes; Djaja, Benny (UNES Law Review, 2023)
This research investigates the implementation of inheritance rights in Indonesia with a focus on the role of customary law, religious law, and positive law in the distribution of inheritance. The research findings illustrate the complexity of the property inheritance system which is influenced by local norms, traditional traditions and religious values. Although Indonesia has national regulations governing inheritance rights, customary law often dominates the division of property in various regions, creating significant variations. Religious law, especially Islamic law, also plays a key role, although implementation varies across different Muslim communities. This research highlights the problem of gender inequality in the inheritance of property and the complexity of modern family structures as the main factors influencing the implementation of inheritance rights. In addition, the economic impact of inheritance rights is highlighted, with particular attention to property management, fair distribution, and protection of heirs' rights. Policy recommendations include legal reform, increasing public awareness, and empowering women to create a more inclusive and fair inheritance rights system in Indonesia.